2007
DOI: 10.1590/s1415-54192007000300012
|View full text |Cite
|
Sign up to set email alerts
|

Estudo comparativo da resistência adesiva da interface resina/braquete, sob esforços de cisalhamento, empregando três resinas compostas e três tipos de tratamento na base do braquete

Abstract: OBJETIVO: considerando que, até o momento, a união braquete/resina é conseguida mecânica e quimicamente, esse estudo propôs avaliar: 1) a eficiência da metodologia empregada para avaliação da força de união da interface resina/braquete; 2) a resistência adesiva da interface resina/braquete sob esforços de cisalhamento, empregando três marcas comerciais de resina composta (Concise ortodôntico, Transbond-XT e Filtek-Z-250); 3) o efeito, nesta resistência adesiva, do jateamento com óxido de alumínio, aplicado na … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0
7

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 9 publications
2
6
0
7
Order By: Relevance
“…These findings are similar to Mondelli and Feitas 11 and Valletta et al, 24 but confront with the results obtained from Giannini and Francisconi 7 research, wherein the Concise TM orthodontic composite appeared stronger than Transbond TM XT composite. For the Alpha Plast and Natural Ortho composites, no evident research was found in the literature.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These findings are similar to Mondelli and Feitas 11 and Valletta et al, 24 but confront with the results obtained from Giannini and Francisconi 7 research, wherein the Concise TM orthodontic composite appeared stronger than Transbond TM XT composite. For the Alpha Plast and Natural Ortho composites, no evident research was found in the literature.…”
Section: Discussionsupporting
confidence: 90%
“…These findings are conflicting when compared to those obtained by Mondelli and Feitas,11 who claim that the weakest link in the orthodontic bonding is in the interface composite/bracket, reiterating that the adhesive interface is critical in terms of resistance.…”
Section: Resultsmentioning
confidence: 73%
“…6,9 Nonetheless, adhesive systems similar to orthodontic systems, such as flow systems, were compared with the Transbond TM XT orthodontic resin, and the results indicated no statistical differences in shear bond strength for most of the systems tested, and no increase in the bonding failure rates. 23 In a comparative study with several systems, Correr Sobrinho et al 11 compared Z100 restorative resin with Transbond TM XT.…”
Section: Discussionmentioning
confidence: 99%
“…At present, there are several resinous systems on the market intended specifically for bonding orthodontic accessories, and scientifically proven to be effective. [3][4][5][6][7][8][9] However, although orthodontic adhesives have a basic formula similar to that of resin composites commonly used in clinical restorative procedures, they are more expensive and are commercially available only from suppliers dealing exclusively with orthodontic materials. For this reason, and possibly also because of their different consistency, not all professionals are familiar with their use and do not choose to use them on a regular basis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation